Electronic band structure and optical gain of GaNxBiyAs1−x−y/GaAs pyramidal quantum dots - Song, Zhi-Gang (2016)
The electronic band structure and optical gain of GaNxBiyAs1−x−y/GaAs pyramidal quantum dots(QDs) are investigated using the 16-band k ⋅ pmodel with constant strain. The optical gain is calculated taking both homogeneous and inhomogeneous broadenings into consideration. The effective band gap falls as we increase the composition of nitrogen (N) and bismuth (Bi) and with an appropriate choice of composition we can tune the emission wavelength to span within 1.3 μm–1.55 μm, for device application in fiber technology. The extent of this red shift is more profound in QDs compared with bulk material due to quantum confinement. Other factors affecting the emission characteristics include virtual crystal, strain profile, band anticrossing (BAC), and valence band anticrossing (VBAC). The strain profile has a profound impact on the electronic structure, specially the valence band of QDs, which can be determined using the composition distribution of wave functions. All these factors eventually affect the optical gain spectrum. With an increase in QD size, we observe a red shift in the emission energy and emergence of secondary peaks owing to transitions or greater energy compared with the fundamental transition.